Prediction of future risk of insulin resistance and metabolic syndrome based on Korean boy's metabolite profiling. Issue 4 (July 2015) - Lee, AeJin; Jang, Han Byul; Ra, Moonjin; Choi, Youngshim; Lee, Hye-Ja; Park, Ju Yeon; Kang, Jae Heon; Park, Kyung-Hee; Park, Sang Ick; Song, Jihyun
Summary: Objective: Childhood obesity is strongly related to future insulin resistance and metabolic syndrome. Thus, identifying early biomarkers of obesity-related diseases based on metabolic profiling is useful to control future metabolic disorders. We compared metabolic profiles between obese and normal-weight children and investigated specific biomarkers of future insulin resistance and metabolic syndrome. Methods: In all, 186 plasma metabolites were analysed at baseline and after 2 years in 109 Korean boys (age 10.5 ± 0.4 years) from the Korean Child Obesity Cohort Study using the AbsoluteIDQ™ p180 Kit. Results: We observed that levels of 41 metabolites at baseline and 40 metabolites at follow-up were significantly altered in obese children ( p < 0.05). Obese children showed significantly higher levels of branched-chain amino acids (BCAAs) and several acylcarnitines and lower levels of acyl–alkyl phosphatidylcholines. Also, baseline BCAAs were significantly positively correlated with both homeostasis model assessment for insulin resistance (HOMA-IR) and continuous metabolic risk score at the 2-year follow-up. In logistic regression analyses with adjustments for degree of obesity at baseline, baseline BCAA concentration, greater than the median value, was identified as a predictor of future risk of insulin resistance and metabolic syndrome. Conclusion: High BCAA concentration could be "early" biomarkers for predicting future metabolic diseases.